2014
DOI: 10.3389/fendo.2014.00008
|View full text |Cite
|
Sign up to set email alerts
|

Central and Direct Regulation of Testicular Activity by Gonadotropin-Inhibitory Hormone and Its Receptor

Abstract: Gonadotropin-inhibitory hormone (GnIH) was first identified in Japanese quail to be an inhibitor of gonadotropin synthesis and release. GnIH peptides have since been identified in all vertebrates, and all share an LPXRFamide (X = L or Q) motif at their C-termini. The receptor for GnIH is the G protein-coupled receptor 147 (GPR147), which inhibits cAMP signaling. Cell bodies of GnIH neurons are located in the paraventricular nucleus (PVN) in birds and the dorsomedial hypothalamic area (DMH) in most mammals. GnI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 100 publications
(143 reference statements)
2
36
0
Order By: Relevance
“…The inhibition of testicular activities induced by RFRP3 is not a result of generalized toxicity, as even a higher dose of RFRP3 caused no deleterious effects on the histology of liver and serum AST and ALT activity compared with control mice. The antigonadal function of GnIH/RFRP3 was demonstrated previously in male quail (Ubuka et al , 2014, Syrian Hamster (Zhao et al 2010), and female mice (Singh et al 2011b).…”
Section: Figuresupporting
confidence: 63%
See 2 more Smart Citations
“…The inhibition of testicular activities induced by RFRP3 is not a result of generalized toxicity, as even a higher dose of RFRP3 caused no deleterious effects on the histology of liver and serum AST and ALT activity compared with control mice. The antigonadal function of GnIH/RFRP3 was demonstrated previously in male quail (Ubuka et al , 2014, Syrian Hamster (Zhao et al 2010), and female mice (Singh et al 2011b).…”
Section: Figuresupporting
confidence: 63%
“…A hypothalamic dodecapeptide (12 amino acids) having LPXRFamide motif at its C-terminal end was isolated from quail brain in the year 2000, which inhibits gonadotropin release and thus was named as gonadotropin-inhibitory hormone (GnIH) (Tsutsui et al 2000). GnIH, acting via GPR147, can suppress the testosterone secretion and spermatogenesis by acting at all levels of the hypothalamic-pituitarygonadal axis of birds and mammals (for reviews, see Tsutsui (2009), Tsutsui et al (2010a,b), and Ubuka et al (2014)). GnIH orthologous peptides that possess LPXRFamide (XZL or Q) motif at their C-termini have been documented in mammals including primates and humans and other vertebrates (for reviews, see Tsutsui (2009) and Tsutsui et al (2010a,b)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent observations pinpoint mid to late March (Krause et al, 2015b). Both gonadotropins and testosterone are required for spermatogenesis (Ubuka et al, 2014), and our results show that plasma testosterone increases in Z. l. nuttalli by week 8 and DHT increases 4 weeks later (Fig. 3B,C).…”
Section: Timing Of Development and Expression Of Breedingsupporting
confidence: 61%
“…89 Two forms of GnIH (RFRP-1 and RFRP-3) have been identified in the human hypothalamus and are able to regulate the HPG axis in men. 90 Hinuma et al 91 identified a specific receptor for mammalian GnIH that was identical to the previously-described receptor, GPR147. 92 The molecular details of GnIH are eloquently described elsewhere.…”
Section: The Hpa Axis and Male Fertilitymentioning
confidence: 70%